Pengaruh Gaya Mengajar Komando terhadap Gerak Dasar pada Teknik Menendang Bola dengan Punggung Kaki Bagian Dalam Permainan Sepak Bola Peserta Didik SMA Negeri 1 Guru Lombok Kalawat - Steven Vhiktor Stevanus Anthoni (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
This study aims to examine the application of command teaching style in improving the ability of basic movements of kicking the ball with the instep in soccer games. The method in this research is experimental method. The samples used were students of SMA Negeri 1` Guru Lombok Kalawat in the academic year 2024/2025 totaling 20 samples, divided into two groups, namely the experimental group with a command teaching style totaling 10 samples and a control group that did not get treatment totaling 10 samples. The research time was one month with a frequency of three times a week. The research design used was “Randomized control group pre - test and post - test design.” The instrument in this study was the “basic motion test of kicking the ball with the instep in a soccer game.” The data analysis technique used is the t-test statistical analysis technique, before the t-test is carried out, it first begins with testing the analysis requirements, namely the data normality test and the variance homogeneity test. The results of this study indicate that the average increase in the ability of basic movements to kick the ball with the instep of the foot in the soccer game of the experimental group using the command teaching style is better than the average increase in the ability of basic movements to kick the ball with the instep of the foot in the soccer game of the control group who did not get treatment.